A PSICODINÂMICA DO TRABALHO E A DIALÉTICA PRAZER E SOFRIMENTO: um estudo junto a advogados especializados em Direito do Trabalho - SOMERA, VALÉRIA DE CARVALHO OLIVEIRA (2018)
The present work aimed to investigate the processes of pleasure and suffering related to the relationships at work and the consequences of such to people’s health. The theoric approach that supports the development of the research was in line with the Dejours’ that, since seventies, by psychopathology of work, and then in the nineties, by psychodynamics of work, supports itself upon the illnesses related to work, a phenomenon found within workers regardless of their professional category. In this research, that second moment in the elaborations proposed by Christophe Dejours was privileged. The participants of the proposed project are lawyers that worked in a law firm in São Paulo city downtown that joined as associates and not as employees. The research, exploratory, had a target on how these lawyers realized and dealed with the coherence with the job proposal along the time they worked in the firm, from December 2010 until January 2015. From that target, many others unfolded, which were mainly to identify and analyze to which capacity each individual could or could not develop suffering and transform it into pleasure. Then, the current work seeks to understand if the processes of suffering turned to diseases and which defense mechanism was triggered by each interviewed lawyer. Lastly, the study also focused on identifying the possible similarities between the experiences reported by the interviewed lawyers and the biggest changes occurred in the people management in the work environment spread during the transition from eighties in different the different work spaces. The criteria to choose the lawyers for the research took account of those which in a certain period in their careers, between December of 2010 and January of 2015, worked in the same firm, but no longer have any ties with the referred office. Another criteria used favored those that, from the analysis executed by the responsible researcher, presented: characteristics related to mental issues; declared themselves “psychically” ill; indicated the use of chemical substances, such as antidepressants and anxiolytics; reported the lack of desire to remain in their occupation due to feeling the violation of their rights, or even manifested a feeling of helplessness from a lack of legal support. The results of the research, obtained by semi-structured interviews, pointed to recurrent speeches marked by ambivalent feelings about their specific academic choice. Some of the interviewed presented a feeling of helplessness in their speech, even though it may seem incongruous admitting that professionals prepared to protect the laws in force in the society they live in see themselves destitute of their own rights. It was also observed, between these workers, the presence of a gap between what is formally expected in the work relationship resulting of the bond as an associate and what was in fact executed in the routine work of the profession.